Asksia AI LOGO

Sia

keyuxuandani's Question
Math
Posted 2 months ago

16:53 12月15日周日
91%91 \%
囚
0455_s20_qp_22
hw2-derivative
Eco经济ig课本
HW-Differentiation
75. What is the slope of the tangent to the curve sin(πx)+9cos(πy)=x2y\sin (\pi x)+9 \cos (\pi y)=x^{2} y at (3,1)(3,-1) ?
(A) π96\frac{\pi-9}{6}
(B) 6π9\frac{6}{\pi-9}
π(0)9π\pi(0)-9 \pi
(C) 6π9\frac{6-\pi}{9}
(D) 96π\frac{9}{6-\pi}
57. Find dydx\frac{d y}{d x} if x2y23x=5x^{2} y^{2}-3 x=5.
(A) 2xy232x2y\frac{2 x y^{2}-3}{2 x^{2} y}
2xy2+2yyy=02 x y^{2}+2 y y y=0
(B) 32xy22x2y\frac{3-2 x y^{2}}{2 x^{2} y} dydx=32xy22x2y\frac{d y}{d x}=\frac{3-2 x y^{2}}{2 x^{2} y}
(C) 23xy22x2y\frac{2-3 x y^{2}}{2 x^{2} y}
(D) 2x2y32x2y\frac{2 x^{2} y-3}{2 x^{2} y}
77. If f(x)=x2f(x)=\frac{\sqrt{x}}{2} and g(x)=cosxg(x)=\cos x, find [f(g(x))][f(g(x))] '.
(A) sinx4cosx\frac{\sin x}{4 \sqrt{\cos x}}
(B) sinx4cosx-\frac{\sin x}{4 \sqrt{\cos x}}
(C) sinx2cosx-\frac{\sin x}{2 \sqrt{\cos x}}
(D) sinxcosx1\frac{\sin x \sqrt{\cos x}}{1}
Sign in to unlock the answer
Answer from Sia
Posted 2 months ago
Solution by Steps
step 2
Differentiating both sides with respect to x x , we get πcos(πx)9πsin(πy)dydx=2xy+x2dydx \pi \cos(\pi x) - 9\pi \sin(\pi y) \frac{dy}{dx} = 2xy + x^2 \frac{dy}{dx}
step 3
Rearranging the equation gives us dydx(x2+9πsin(πy))=πcos(πx)2xy \frac{dy}{dx} (x^2 + 9\pi \sin(\pi y)) = \pi \cos(\pi x) - 2xy
step 4
Solving for dydx \frac{dy}{dx} yields dydx=πcos(πx)2xyx2+9πsin(πy) \frac{dy}{dx} = \frac{\pi \cos(\pi x) - 2xy}{x^2 + 9\pi \sin(\pi y)}
step 5
Substituting (3,1) (3, -1) into the equation gives dydx=πcos(3π)2(3)(1)32+9πsin(π)=π+69=π+69 \frac{dy}{dx} = \frac{\pi \cos(3\pi) - 2(3)(-1)}{3^2 + 9\pi \sin(-\pi)} = \frac{\pi + 6}{9} = \frac{\pi + 6}{9}
step 6
Evaluating this expression leads us to find the slope at the point (3,1) (3, -1) is 6π9 \frac{6 - \pi}{9}
75 Answer
C
Solution by Steps
step 2
Differentiating both sides gives 2xy2+2x2ydydx3=0 2xy^2 + 2x^2y \frac{dy}{dx} - 3 = 0
step 3
Rearranging the equation results in 2x2ydydx=32xy2 2x^2y \frac{dy}{dx} = 3 - 2xy^2
step 4
Solving for dydx \frac{dy}{dx} yields dydx=32xy22x2y \frac{dy}{dx} = \frac{3 - 2xy^2}{2x^2y}
76 Answer
B
Solution by Steps
step 2
This gives us f(g(x))=f(cosx)=cosx2 f(g(x)) = f(\cos x) = \frac{\sqrt{\cos x}}{2}
step 3
Therefore, the final expression for [f(g(x))] [f(g(x))] is cosx2 \frac{\sqrt{\cos x}}{2}
77 Answer
Blank
Key Concept
Implicit Differentiation
Explanation
Implicit differentiation allows us to find the derivative of a function defined implicitly, which is essential for finding slopes of tangents to curves.
Key Concept
Chain Rule
Explanation
The chain rule is used to differentiate composite functions, allowing us to evaluate f(g(x)) f(g(x)) effectively.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question